(untitled) (Journal on Excellence in College Teaching, 2024)
Foundational undergraduate courses in chemistry and mathematics are gateways to a number of lucrative majors and pre-professional programs. Historically, however, students often struggle with these disciplines and can benefit from alternate approaches to examining their learning strategies. This article describes the use of exam wrappers—reflective activities performed by students after taking exams—to improve students’ knowledge and regulation of metacognition—the process of thinking about thinking. Quantitative and qualitative analyses of student learning are described, along with suggestions for other practitioners and researchers to consider in coaching metacognitive strategies.